The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00737-016-0698-1
|View full text |Cite
|
Sign up to set email alerts
|

Promoting improved social support and quality of life with the CenteringPregnancy® group model of prenatal care

Abstract: This prospective cohort study compared women participating in CenteringPregnancy® group prenatal care (N = 120) with those in standard individual care (N = 221) to determine if participation in Centering was associated with improvements in perceived social support and quality of life, with concomitant decreases in screens of postpartum depression and improvements in breastfeeding rates. Participants completed surveys at the onset of prenatal care, in the late third trimester and in the postpartum period. Cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 59 publications
2
26
1
Order By: Relevance
“…However, our findings regarding improved patient experience with Access to Care, driven by their ability to see their provider quickly ("saw provider within 15 minutes of appointment") reflects previous research citing the importance of the amount of time saved waiting for care for women in Centering (22). Similarly, the results of the qualitative analysis are consistent with previous findings reporting improvements in social support for women in Centering programs in military health settings (13,22). Our findings from interviews with providers and implementation staff also reflect those of previous research demonstrating the challenges of finding dedicated program space as well as the importance of support from MTF leadership (21).…”
Section: Discussionsupporting
confidence: 89%
“…However, our findings regarding improved patient experience with Access to Care, driven by their ability to see their provider quickly ("saw provider within 15 minutes of appointment") reflects previous research citing the importance of the amount of time saved waiting for care for women in Centering (22). Similarly, the results of the qualitative analysis are consistent with previous findings reporting improvements in social support for women in Centering programs in military health settings (13,22). Our findings from interviews with providers and implementation staff also reflect those of previous research demonstrating the challenges of finding dedicated program space as well as the importance of support from MTF leadership (21).…”
Section: Discussionsupporting
confidence: 89%
“…This suggested an impact of the prenatal sessions beyond the meeting rooms to family and community levels, which could engender more social support for mothers. Interestingly, Chae et al . have shown that group prenatal care confers higher perception of family and friends’ support compared to traditional prenatal care.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Social support is linked to improvements in maternal quality of life, higher rates of continued breastfeeding, and breastfeeding self-efficacy. 2–4 Adequate social support promotes mental health in the perinatal period by reducing low mood and anxiety and helping women manage feelings of isolation and disempowerment. 1 As women transition to motherhood, social support also enhances maternal competence by providing encouragement, promoting self-esteem, and decreasing stress.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to traditional models of prenatal care, group prenatal care (GPNC), where women receive care in small groups and participate in group discussion covering a variety of health topics related to pregnancy, has been shown to boost women's perceptions of social support. 2 , 14 CenteringPregnancy, an evidence-based GPNC model, provides prenatal care through a supportive group process. 15 Health care providers facilitate discussion and engage in interactive learning activities with group members ( i.e.…”
Section: Introductionmentioning
confidence: 99%